Tinjauan Sistem Dan Prosedur Penggajian Dan Perhitungan PPh 21 Pada Universitas X - Khairunnisa, Syifa; Herawati, Heti (Jurnal Aplikasi Bisnis Kesatuan, 2025)
The wage system is the process of managing everything related to the payment of employees and the reporting of wage taxes. The wage system is essential in order to help the wage process better. The purpose of this research is to know the System and Procedures of Payment and the documents used, then to find out any obstacles that occur in the system of pay, as well as to know whether the calculation of PPh 21 at the University of X is accurate or not with the Regulations of the Taxation Legislation in force today. The results of this survey show that the remuneration system at X University already uses the Fingerprint Engine, the GPP Application, and the Payroll System. The system is already able to help the work of certain departments/divisions to avoid difficulties in making payrolls, calculating wages, reporting wages and preparing tax deductions. The system used is very accurate, and good. The remuneration procedures at the University X have been run by their respective divisions to avoid manipulation and fraud. As for the documents that make up the salary, they are complete and detailed. Then the remuneration procedures at the University X have been implemented in accordance with its functions, the functions consist of the function of staffing, function of payroll maker, accounting and financial functions. And there are barriers that the University of X is experiencing, however, that can be controlled. As well as PPh21 calculations, the result of the calculations is NIHIL due to net income a year below the PTKP income. The results of the evaluation in this study show that in the fingerprint system there are only those who do not do absences but the employees still want their salary to remain full. However, the SDM or Finance department at the University of X must be aware of that. Nevertheless, the employee won't get his rights because of his own mistakes. The University of X must provide even more rigorous supervision so that this will not happen again in the future.   Keywords: pay system, ASN, pay document, PPh 21